A1 and A2 milk caseins-comparative FTIR and spectroflourimetry analysis - SHIVANGI JOSHI; FAIZAN MANSURI; ADITI KULKARNI; SURUCHI JAMKHEDKAR (Indian Journal of Animal Sciences, 2021)
Around 35% of the total caseins are Î²-caseins, which are further classified as A1 Î²-caseins and A2 Î²-caseins, based on differences in the amino acid composition of both. A2 is the wild type genetic variant of Î²-casein while A1 is the mutant. The present study aimed at the isolation of A1 and A2 casein from different cow milk sources and its characterization by using simple chemical techniques, viz. FTIR and spectrofluorimetry. The commercial milk sample from Bos indicus (Gir) (A2) was obtained from Bombay Panjrapole, Mumbai and two commercially available packaged cow milk samples (pasteurized, skimmed) namely from Gokul and Mother Dairy (A1) were also obtained for comparison analysis from the local market. The isolation of casein was performed by standard method and analyzed using SDS-PAGE, FTIR and spectrofluorimetry. There was evidence that the A2 milk lacked histidine and rich in aromatic amino acids like tryptophan using FTIR and spectrofluorimetry techniques.